Recent advances in antigen targeting to antigen-presenting cells in veterinary medicine - Melgoza-González, Edgar Alonso; Bustamante-Córdova, Lorena; Hernández, Jesús (Frontiers in Immunology, 2023)
Advances in antigen targeting in veterinary medicine have gained traction over the years as an alternative approach for diseases that remain a challenge for traditional vaccines. In addition to the nature of the immunogen, antigen-targeting success relies heavily on the chosen receptor for its direct influence on the elicited response that will ensue after antigen uptake. Different approaches using antibodies, natural or synthetic ligands, fused proteins, and DNA vaccines have been explored in various veterinary species, with pigs, cattle, sheep, and poultry as the most frequent models. Antigen-presenting cells can be targeted using a generic approach, such as broadly expressed receptors such as MHC-II, CD80/86, CD40, CD83, etc., or focused on specific cell populations such as dendritic cells or macrophages (Langerin, DC-SIGN, XCR1, DC peptides, sialoadhesin, mannose receptors, etc.) with contrasting results. Interestingly, DC peptides show high specificity to DCs, boosting activation, stimulating cellular and humoral responses, and a higher rate of clinical protection. Likewise, MHC-II targeting shows consistent results in enhancing both immune responses; an example of this strategy of targeting is the approved vaccine against the bovine viral diarrhea virus in South America. This significant milestone opens the door to continuing efforts toward antigen-targeting vaccines to benefit animal health. This review discusses the recent advances in antigen targeting to antigen-presenting cells in veterinary medicine, with a special interest in pigs, sheep, cattle, poultry, and dogs.